Renewable Energy Solutions for Achieving Net Zero Building - Mubarok, Moh. Wahyu Syafiul; Ramadhani, Shafira; Tsaqif, Muhammad Isa (NBRI Press, 2024)
This paper presents an in-depth analysis of the Jowata architectural concept, designed as a net zero building through the integration of multiple renewable energy systems. Located in Kota Baru Parahyangan, Bandung, the design incorporates passive, active, and renewable energy strategies, focusing on solar photovoltaic (PV) panels, wind turbines, and pico hydro systems to meet the building’s energy needs. Comprehensive simulations, including Global Horizontal Irradiation (GHI) and wind speed analyses, were conducted to optimize the placement and efficiency of these technologies. The Jowata Grid System, supported by the local energy grid, achieves a 71.5% renewable energy offset, resulting in annual CO₂ emissions savings of approximately 23,987 tons. The building's Energy Use Intensity (EUI) is significantly below regional benchmarks, demonstrating the efficiency of the design. This study highlights the effectiveness of combining various renewable energy sources in achieving net zero emissions and offers a blueprint for sustainable building practices in similar climatic regions.